SOSIALISASI KESELAMATAN BERLALU LINTAS BAGI WARGA RW 04 KALIBARU - Suhardiman, Cecep; Sekartaji , Raden Rara Hapsari Tunjung; Novita , Erni; Anggi , Yuri (Inspirasi: Jurnal Pengabdian Masyarakat, 2025)
Traffic safety socialization is a crucial effort to reduce accident rates and increase public legal awareness. This community service activity was conducted in RW 04, Kalibaru Village, North Jakarta, involving lecturers and students from the Faculty of Law at Universitas 17 Agustus 1945 Jakarta. The socialization method involved delivering materials, interactive discussions, and distributing leaflets explaining the rights and obligations of road users based on Law Number 22 Year 2009 concerning Traffic and Road Transportation. The results showed an increased understanding among residents about the importance of traffic safety, mandatoryVehicleequipment, and awareness of legal sanctions for traffic violations. This activity is expected to encourage more orderly traffic behavior and reduce accident risks in the RW 04 Kalibaru area.